1971
DOI: 10.1113/jphysiol.1971.sp009445
|View full text |Cite
|
Sign up to set email alerts
|

The control by internal calcium of membrane permeability to sodium and potassium

Abstract: SUMMARY1. A study has been made of the relationship between the concentration of internal calcium and the permeability of human red cell membranes to sodium and potassium.2. Fresh red cells contain very little calcium, but after being depleted of ATP by ageing they took up calcium from Ringer solution. The entry was unaffected by external sodium and potassium but was markedly pH dependent. When supplied with energy, calcium-loaded cells actively extruded calcium by a saturable process which was also unaffected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
1

Year Published

1972
1972
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(90 citation statements)
references
References 29 publications
(28 reference statements)
5
84
1
Order By: Relevance
“…When erythrocytes were cold-stored in iso-osmotic sucrose or isoosmotic KCI, the rates at which the cells became depleted of ATP were similar ( (Long & Mouat, 1973), enough remained to function as substrate for the Ca2+-activated adenosine triphosphatase and to cause efflux of Ca2+ from Ca2+-loaded cells when these were subsequently incubated at 37°C. In this respect the results differ from those of Lew (1970Lew ( , 1971 and Romero & Whittam (1971), who worked at 37'C and found the ATP contents of the cells to be of prime importance. This apparent discrepancy is most simply explained in terms of temperature.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…When erythrocytes were cold-stored in iso-osmotic sucrose or isoosmotic KCI, the rates at which the cells became depleted of ATP were similar ( (Long & Mouat, 1973), enough remained to function as substrate for the Ca2+-activated adenosine triphosphatase and to cause efflux of Ca2+ from Ca2+-loaded cells when these were subsequently incubated at 37°C. In this respect the results differ from those of Lew (1970Lew ( , 1971 and Romero & Whittam (1971), who worked at 37'C and found the ATP contents of the cells to be of prime importance. This apparent discrepancy is most simply explained in terms of temperature.…”
Section: Discussioncontrasting
confidence: 56%
“…Lew (1970Lew ( , 1971 showed that Ca2+ influx at 37°C from a saline medium occurred only after the cells had become depleted of their ATP content. Romero & Whittam (1971) confirmed this and further demonstrated that for ATP-depleted erythrocytes, also incubated under similar conditions, Ca2+ influx was strongly pH-dependent; it did not occur at pH 7.0 or below, but was appreciable at higher pH values. Long & Mouat (1973), on the other hand, used fresh erythrocytes and worked at low temperature to minimize any interfering effects of cell metabolism.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…But in addition to this principal action, Ca2+ may also cause some increase in JNa' since the resting potential in our experiments was often relatively little changed, or even became a little more positive (coupling artifacts probably exaggerated this effect). In this respect, the motoneurones may behave like red blood cells, in which a rise in free Ca2+ level increases first the K+ permeability and then the Na+ permeability (Whittam, 1968;Romero & Whittam, 1971).…”
mentioning
confidence: 99%